(untitled) (Fiep Bulletin - online, 2012)
This study has the purpose of analyzing teachers’ cognition at Physical Education in regular Education in São João del Rei/MG, regarding to the inclusion of students with special educational needs. Using the questionnaire adapted by Gorgatti et. al. (2004, p.67), from original models of the specialized literature, there was the application of this tool for seventeen teachers of Physical Education, twelve of the public network and five of the particular. This questionnaire involved three aspects: (a) how teacher evaluates his knowledge to deal with children with special educational needs, (b) how teacher understands the acceptance of these children by fellow "normal", and, (c) how the teacher evaluates the conditions of his school for joining the proposal of inclusive education. The results indicate that 41,18% of the teachers believe that their knowledge to deal with special children are enough and about 94,12% of the interviewed like or would like to work with the proposal of inclusive education. Thus, 88,23 % of teachers believe in the benefits of inclusive proposal for all children, however, 94,12 % believe that their schools are not prepared to receive special children. At the end of the study is possible to observe different trends responses among the teachers from the public system and from private schools network.